Politik Hukum Tata Kelola Perizinan Lingkungan Pasca Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja - Nabila Aulia Rahma (Jurnal Hukum Lex Generalis, 2022)
The passage of the Job Creation Law brought about many fundamental changes in economic policy, including environmental licensing. The reason is that there is a fundamental legal political change that is more directed towards the ease of doing business and investing compared to environmental conservation, namely by changing the terminology of environmental licensing to environmental approval. So in this paper, the author will discuss how to analyze the legal politics of environmental licensing governance after the Job Creation Act. The results of this study indicate a change in legal politics in environmental licensing governance after the Job Creation Act which has implications for the business licensing system. So that a legal mapping is needed regarding the ideal concept of environmental permitting to be in accordance with the 1945 Constitution of the Republic of Indonesia.